2004
DOI: 10.1177/107602960401000203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan and Simvastatin on Monocyte-Derived Microparticles in Hypertensive Patients With and Without Type 2 Diabetes Mellitus

Abstract: Monocyte-derived microparticles play an important role in the pathogenesis of diabetic vasculopathy, and angiotensin II receptor blocker and statin have been shown to have a beneficial effect on the angiopathies of hypertension and hyperglycemia in patients with type 2 diabetes mellitus. However, the interaction between angiotensin II receptor blocker and statin, and monocyte-derived microparticles in atherosclerosis is poorly understood. The effects of losartan and simvastatin on circulating concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 54 publications
3
60
0
Order By: Relevance
“…[124] . A few studies have indicated that the levels of monocyte-derived MVs [14,55] , endothelial-derived MVs [74] , and platelet-derived MVs [70,125,126] are increased in patients with diabetic nephropathy. The increase in monocyte-derived MVs is most significant in patients with diabetic nephropathy among the T2DM patients with diabetic microangiopathy, ie, nephropathy, retinopathy, or neuropathy [14] .…”
Section: Mvs In Diabetic Microvascular Complicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…[124] . A few studies have indicated that the levels of monocyte-derived MVs [14,55] , endothelial-derived MVs [74] , and platelet-derived MVs [70,125,126] are increased in patients with diabetic nephropathy. The increase in monocyte-derived MVs is most significant in patients with diabetic nephropathy among the T2DM patients with diabetic microangiopathy, ie, nephropathy, retinopathy, or neuropathy [14] .…”
Section: Mvs In Diabetic Microvascular Complicationsmentioning
confidence: 99%
“…The increase in monocyte-derived MVs is most significant in patients with diabetic nephropathy among the T2DM patients with diabetic microangiopathy, ie, nephropathy, retinopathy, or neuropathy [14] . Elevated levels of endothelial-derived MVs and monocytederived MVs may serve as biomarkers for nephropathy progression in T2DM [14,55,74] . A recent study showed that MVassociated dipeptidyl peptidase-IV (DPP-IV) is the major form of DPP-IV in urine, which is secreted from tubular epithelial cells and is related to early tubular impairment [127] .…”
Section: Mvs In Diabetic Microvascular Complicationsmentioning
confidence: 99%
See 3 more Smart Citations